2013
DOI: 10.1682/jrrd.2011.09.0163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structured vocational services in ex-offender veterans with mental illness: 6-month follow-up

Abstract: Abstract-With more than 200,000 veterans incarcerated, a significant need exists for the development of technologies that help veterans with felony histories return to employment. This study evaluated the effect of three methods of vocational assistance on competitive employment over a 6 mo follow-up period: (1) basic vocational services, (2) self-study using a vocational manual designed for formerly incarcerated veterans, and (3) a group led by vocational staff using the vocational manual. We evaluated 111 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…Assessment of risk of bias confirmed that one study had a low risk of bias (Schaeffer et al ) and three studies a moderate risk of bias (LePage et al, ; LePage et al, ; Evans et al, ). One study was found to have a high risk of bias (Hall et al, ), and it was not possible to assess the risk of bias for one study (Twentyman et al, ) because of poor reporting of the study procedure.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Assessment of risk of bias confirmed that one study had a low risk of bias (Schaeffer et al ) and three studies a moderate risk of bias (LePage et al, ; LePage et al, ; Evans et al, ). One study was found to have a high risk of bias (Hall et al, ), and it was not possible to assess the risk of bias for one study (Twentyman et al, ) because of poor reporting of the study procedure.…”
Section: Resultsmentioning
confidence: 81%
“…There were three randomised controlled trials (Twentyman et al, ; Hall et al, ; Schaeffer et al, ), two non‐randomised but controlled trials (LePage et al, ; LePage et al, ) and one retrospective cohort study (Evans et al, ). It was not possible to ascertain if a sub‐sample of LePage et al () participants also participated in the LePage et al () study. This is a possibility, but for the purposes of this review we have considered them as separate papers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These employers also recommended to employment specialists that they encourage job seekers to be honest as well as help them practice talking about their conviction and about positive changes in their lives since the conviction. Randomized studies have shown these strategies to successfully help Veterans with convictions find employment [13][14].…”
Section: Introductionmentioning
confidence: 99%